2020
DOI: 10.17843/rpmesp.2020.374.5294
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de médicos que realizan el Servicio Rural y Urbano Marginal de Salud en Perú sobre el primer nivel de atención

Abstract: Objetivo: Determinar la percepción de los médicos que realizan el Servicio Rural y Urbano Marginal de Salud (SERUMS) en Perú sobre el trabajo en el primer nivel de atención (PNA) y sus factores asociados. Materiales y métodos: Se realizó un análisis secundario de datos de una muestra de médicos que realizaron el SERUMS el 2016. Para evaluar la variable de interés se utilizó la escala de «Percepción sobre el trabajo en el PNA», cuyos puntajes más altos indican una peor percepción del trabajo en el PNA. Se aplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Notably, SERUMS often marks the rst time GPs assume managerial responsibilities and work extensively with other health professionals, contrasting their previous experiences. This new environment necessitates skills that many GPs lack, as evidenced by a study indicating a decline in their interest in primary care post-SERUMS [4]. This trend may be attributed to insu cient training in essential competencies, adversely affecting GP's self-e cacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SERUMS often marks the rst time GPs assume managerial responsibilities and work extensively with other health professionals, contrasting their previous experiences. This new environment necessitates skills that many GPs lack, as evidenced by a study indicating a decline in their interest in primary care post-SERUMS [4]. This trend may be attributed to insu cient training in essential competencies, adversely affecting GP's self-e cacy.…”
Section: Discussionmentioning
confidence: 99%
“…This program is essential in providing healthcare services in such areas by assigning trained health professionals. Although one study has suggested that the SERUMS has reduced inequity in healthcare for neglected communities [3], several studies highlighted the lack of training from General Practitioners (GPs) for this major task [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…En 2018, más de 570 000 mujeres en todo el mundo fueron diagnosticadas con cáncer de cuello uterino, de las 311 365 mujeres que fallecieron a causa de esta enfermedad, el 90 % vivía en países de en vías de desarrollo (20,21). Por lo que es importante mejorar la política de atención primaria en salud, promover la vacunación contra VPH (22,23), además de mejorar las condiciones de trabajo para el personal de salud e incrementar puestos de trabajo para alcanzar los indicadores de prevención de cáncer de cuello uterino (24)(25)(26).…”
Section: Discussionunclassified